dentification ofDistance Learning Difficulties From the Perspective ofElementary School Students - Maharani, Fuan; Widodo, Arif (Indonesian Research Journal on Education, 2021)
The COVID-19 pandemic has greatly impacted the economy and education in all parts of the world, including Indonesia. This requires the government to change teaching and learning policies by conducting distance learning, including for elementary school education. This study aims to identify barriers for elementary school students in implementing distance learning during the Covid-19 pandemic. Data collection in this study used qualitative methods, with interview techniques and closed questionnaires. The research subjects used were 45 students from 16 elementary school institutions in West Nusa Tenggara. The results shown from this study are the obstacles experienced by students in conducting distance learning, including difficulty in understanding teaching materials, lack of explanation from the teacher, no place to ask questions, no friends to discuss with, often scolded by parents, and assignments given. a huge amount.